2010
DOI: 10.1111/j.1399-3038.2010.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine exposure to polycyclic aromatic hydrocarbons, fine particulate matter and early wheeze. Prospective birth cohort study in 4-year olds

Abstract: The main goal of the study was to determine the relationship between prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) measured by PAH-DNA adducts in umbilical cord blood and early wheeze. The level of PAH-DNA adducts in the cord blood is assumed to reflect the cumulative dose of PAHs absorbed by the fetus over the prenatal period. The effect of prenatal PAH exposure on respiratory health measured by the incidence rate ratio (IRR) for the number of wheezing days in the subsequent four year follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 44 publications
0
55
1
1
Order By: Relevance
“…The highest levels of PAHs during pregnancy were associated with a reduced FEV 1 and a reduced FEV 25–75 40. The same authors have reported that the number of wheezing days during the first 2 years of life was positively associated with the prenatal level of PAH-adducts (incidence rate ratio [IRR] =1.69; 95% CI: 1.52–2.88) 41. Correlations among personal exposure, pre-and postnatal PAH, and the severity of wheezing and recurrent wheezing were also studied by the same group of researchers and suggested that prenatal exposure may trigger and intensify the symptoms resulting from postnatal exposure.…”
Section: Methodsmentioning
confidence: 94%
“…The highest levels of PAHs during pregnancy were associated with a reduced FEV 1 and a reduced FEV 25–75 40. The same authors have reported that the number of wheezing days during the first 2 years of life was positively associated with the prenatal level of PAH-adducts (incidence rate ratio [IRR] =1.69; 95% CI: 1.52–2.88) 41. Correlations among personal exposure, pre-and postnatal PAH, and the severity of wheezing and recurrent wheezing were also studied by the same group of researchers and suggested that prenatal exposure may trigger and intensify the symptoms resulting from postnatal exposure.…”
Section: Methodsmentioning
confidence: 94%
“…Eight nonvolatile PAHs (PAHs with more than 4 rings: MW 228-278) were selected as target compounds due to their abundance in traffic emissions and their adverse health effects observed in young children [5][6][7][8][24][25][26] [27]. Detailed analytical protocols employed for the measurement of PAHs have been reported elsewhere [28] and a brief summary is given here.…”
Section: Sample Analysismentioning
confidence: 99%
“…However, the uncertainties surrounding the precise physical and chemical components of PM, which are responsible for observed health risks, make it challenging to understand the causal relationships between PM exposure and health effects. Among numerous toxic chemical components of PM, polycyclic aromatic hydrocarbons (PAHs) have received particular attention because recent studies implicated that prenatal PAH exposure, specifically Σ 8 PAHs (the sum of 8 nonvolatile PAHs; ), were associated with respiratory symptoms, low birth weight, and deficits in neurodevelopment and cognition in young children [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In support of the latter hypothesis, there are many epidemiological studies showing an association between various in utero exposures and asthma susceptibility 512 . Among prenatal insults with linkage to asthma, solid and consistent epidemiological evidence has been provided for exposure to traffic-related pollution, including diesel exhaust 58 . Mothers who lived near highways during pregnancy are more likely to have children with asthma 5 .…”
Section: Introductionmentioning
confidence: 99%